2020
DOI: 10.1002/jor.24748
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in ACL morphology during skeletal growth and maturation are different between females and males

Abstract: Despite a well-established role of anterior cruciate ligament (ACL) anatomy on its biomechanics, little is known on how ACL anatomy develops and changes during skeletal growth. We hypothesized that ACL size and orientation will change by age during skeletal growth and maturation with different trends in males vs females. Magnetic resonance images of 269 unique knees (3-18 years old; 51% female) were used to measure ACL length, cross-sectional area, length-to-cross-sectional area ratio, and elevation angles. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
53
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 46 publications
(89 reference statements)
14
53
1
Order By: Relevance
“…These studies have also found that while ACL length and CSA are similar between the sexes during childhood, both measurements are 15-25% larger in males during late adolescence. [6][7][8] Similarly, our findings showed that ACL length and CSA were 15% and 23% larger, respectively, in males than females during late adolescence. Additionally, in agreement with the current study, human studies found little to no (0-3°) impact of sex on ACL inclination angle.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…These studies have also found that while ACL length and CSA are similar between the sexes during childhood, both measurements are 15-25% larger in males during late adolescence. [6][7][8] Similarly, our findings showed that ACL length and CSA were 15% and 23% larger, respectively, in males than females during late adolescence. Additionally, in agreement with the current study, human studies found little to no (0-3°) impact of sex on ACL inclination angle.…”
Section: Discussionsupporting
confidence: 71%
“…The changes in ACL morphology with respect to growth and sex from our study are also consistent with skeletally immature human data. Studies have shown approximately two-fold increases in ACL length and CSA, [6][7][8] and approximately 15° increases in angular inclination 8; 33 from early youth to late adolescence. These studies have also found that while ACL length and CSA are similar between the sexes during childhood, both measurements are 15-25% larger in males during late adolescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the age in the ACLD group was greater than the ACLI group, so that a confounding factor might have been brought in this case-control study. However, the age difference could be explained by the strong association between the grade of ACL degeneration and the grade of knee osteoarthritis [ 22 ], where a greater age is related to a greater degeneration of the knee [ 23 , 24 ]. Third, the slice thickness of the MRI was 4 mm, which could create bias in PATS measurements.…”
Section: Discussionmentioning
confidence: 99%
“…A greater cross-sectional area-to-length ratio was increased in males, and this difference between males and females increased with age. 1 A greater cross-sectional area would seem to correlate with more strength, but it is a hypothesis that would need to be tested. It would also be interesting to compare injury rates in adults vs children of different genders to see if this change is truly related to the cross-sectional area.…”
mentioning
confidence: 99%